Pharmacognostical and phytochemical evaluation of Aerial parts of Rhynchosia nummularia (L.) Dc. - S. VINOTH KUMAR,; V. GOPAL,; N. DEVANNA, (International Journal of Pharma and Bio Sciences, 2018)
Rhynchosia nummularia (L.) DC. (Family: Fabaceae) also called as Glycine nummularia or Nomismia nummularia is found in India specially in southern states like Tamil nadu and Andhra pradesh. It is used for wide range of diseased conditions, but unfortunately very limited literature is available regarding it. The present study attempts to investigate pharmacognostical characters, including morphological, microscopical evaluation of stem, leaf, petiole of selected medicinal plant. It revealed that presence of stomata, trichomes, tannins, vascular bundles, etc. Physical evaluation moisture content, ash values, extractive values and Loss on drying were studied. The presence of alkaloids, carbohydrate, flavonoids, proteins and phenolic compounds were confirmed during preliminary phytochemical screening. These observations would be of immense value in the qualitative and quantitative parameters and serve as the important information to identify and to determine the quality and purity of the plant material in the future. It also signify the important information of the closely related other species and varieties.